2011 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2011
DOI: 10.1109/isbi.2011.5872579
|View full text |Cite
|
Sign up to set email alerts
|

Practical parallel imaging compressed sensing MRI: Summary of two years of experience in accelerating body MRI of pediatric patients

Abstract: For the last two years, we have been experimenting with applying compressed sensing parallel imaging for body imaging of pediatric patients. It is a joint-effort by teams from UC Berkeley, Stanford University and GE Healthcare. This paper aims to summarize our experience so far. We describe our acquisition approach: 3D spoiled-gradient-echo with poisson-disc random undersampling of the phase encodes. Our re-construction approach: ℓ1-SPIRiT, an iterative autocalibrating parallel imaging reconstruction that enfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 8 publications
4
117
0
Order By: Relevance
“…Without shift-invariance property, the signal restored using the orthogonal discrete wavelet transform will exhibit much more artifacts in denoising [11,12]. Within the field of MRI, some researchers have utilized SIDWT to reconstruct MR images and found it superior than its orthogonal counterpart in noise suppression and artifacts reduction [5,36,[42][43][44]. In all the experiments, Daubechies wavelets with 4 decomposition levels are utilized in SIDWT.…”
Section: A Main Resultsmentioning
confidence: 99%
“…Without shift-invariance property, the signal restored using the orthogonal discrete wavelet transform will exhibit much more artifacts in denoising [11,12]. Within the field of MRI, some researchers have utilized SIDWT to reconstruct MR images and found it superior than its orthogonal counterpart in noise suppression and artifacts reduction [5,36,[42][43][44]. In all the experiments, Daubechies wavelets with 4 decomposition levels are utilized in SIDWT.…”
Section: A Main Resultsmentioning
confidence: 99%
“…Vasanawala et al (2011) recently reported a successful combination of parallel imaging, compressed sensing and a GPU implementation in this realm. Kowalik et al (2012) also used GPU accelerated reconstruction of parallel imaging in order to monitor the flow of cardiac output in real-time.…”
Section: Mrimentioning
confidence: 99%
“…For instance, due to the potential of higher signal-to-noise ratio at 7 T, higher resolution is often pursued (most commonly to assess the hippocampal morphometry of patients with dementia), which leads to longer scan times for a patient population that can only tolerate short examinations. Many hardware technologies and software techniques are being developed to deal with the increasing scan times, including coil-based acceleration schemes, 7,54,58,78 compressed sensing, 91 multiband and multislice excitation, 62,77 and improved coil design.…”
Section: -T Mri Limitations and Challengesmentioning
confidence: 99%